Thymic development of human natural killer T cells: recent advances and implications for immunotherapy - Pellicci, Daniel G.; Tavakolinia, Naeimeh; Perriman, Louis; Berzins, Stuart P.; Menne, Christopher (Frontiers in Immunology, 2024)
Invariant natural killer T (iNKT) cells are a subset of lipid-reactive, unconventional T cells that have anti-tumor properties that make them a promising target for cancer immunotherapy. Recent studies have deciphered the developmental pathway of human MAIT and Vγ9Vδ2 γδ-T cells as well as murine iNKT cells, yet our understanding of human NKT cell development is limited. Here, we provide an update in our understanding of how NKT cells develop in the human body and how knowledge regarding their development could enhance human treatments by targeting these cells.